Socially productive activities and subjective well-being among rural elderly in Perak, Malaysia - Nur Syakirah Hamzah (2020)
The purpose of this research is study the relationship between socially productive activities and subjective wellbeing among rural elderly in Perak, Malaysia. Quantitative approach and survey method were used in this research. The questionnaire was distributed by simple random sampling to 480 people age 50 to 80 years old located in Muallim, Perak Tengah and Hulu Perak. Data were analysed using descriptive and inferential statistics such as mean, standard deviation, t-test and Pearson correlation. Findings show that respondents agreed that their level of wellbeing is high (M=3.14, SD=0.41). Nevertheless, there is no difference in the wellbeing of the elderly based on their employment status. The findings also show that there is moderate positive relationship between volunteering activities and subjective wellbeing r(480)=0.52(p>0.05). In conclusion, the study found that elderly experiences high level of wellbeing when they participate in voluntary activities. In implication, elderly should increase their involvement in optional activities as it has positive impact on maintaining their subjective wellbeing.